The role of procalcitonin in identifying high‐risk cancer patients with febrile neutropenia: A useful alternative to the multinational association for supportive care in cancer score - Patrick Chaftari (Wiley, 2021)
Abstract Background The Multinational Association for Supportive Care in Cancer (MASCC) risk index has been utilized to determine the risk for poor clinical outcomes in patients with febrile neutropenia (FN) in an emergency center (EC). However, this index comprises subjective elements and elaborated metrics limiting its use in ECs. We sought to determine whether procalcitonin (PCT) level (biomarker of bacterial infection) with or without lactate level (marker of inadequate tissue perfusion) offers a potential alternative to MASSC score in predicting the outcomes of patients with FN presenting to an EC. Methods We retrospectively identified 550 cancer patients with FN who presented to our EC between April 2018, and April 2019, and had serum PCT and lactate levels measured. Results Compared with patients with PCT levels <0.25 ng/ml, those with levels ≥0.25 ng/ml had a significantly higher 14‐day mortality rate (5.2% vs. 0.7%; p = 0.002), a higher bloodstream infection (BSI) rate, and a longer hospital length of stay (LOS). Logistic regression analysis showed that patients with PCT levels ≥0.25 ng/ml and lactate levels >2.2 mmol/L were more likely to be admitted and have an LOS >7 days, BSI, and 14‐day mortality than patients with lower levels. PCT level was a significantly better predictor of BSI than MASSC score (p = 0.003) or lactate level (p < 0.0001). Conclusions Procalcitonin level is superior to MASCC index in predicting BSI. The combination of PCT and lactate levels is a good predictor of BSI, hospital admission, and 14‐day mortality and could be useful in identifying high‐risk FN patients who require hospital admission.